1989
DOI: 10.1136/bmj.299.6699.591
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle driving among diabetics taking insulin and non-diabetics.

Abstract: parental blood pressure has been measured. It is interesting, however, that the relation between birth weight, maternal age, and birth rank and blood pressure were largely unaffected by adjustment for reported parental history of high blood pressure and seemed to be similar in children with and without a maternal history of hypertension. These findings suggest that the means by which familial influences on blood pressure are mediated are quite separate from those of the other factors discussed. Conclusions-Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 11 publications
3
31
0
2
Order By: Relevance
“…As there is a reasonably large body of literature showing that hypoglycemia occurs more often among individuals treated with insulin than among those treated by pharmacotherapy or diet alone, one might reasonably expect to observe that individuals with insulin-treated diabetes are at higher risk for a motor vehicle crash when compared with individuals who control their diabetes by other means. Five of the 13 included studies provided separate crash risk data for drivers who were insulin-treated (Cox, 2003;Eadington & Frier, 1989;Laberge-Nadeau, 2000;Songer, 1988;Stevens, 1989) allowing us to estimate of the risk ratio associated with this subpopulation of drivers.…”
Section: Figure 1 Crash Risk In Drivers With Diabetes Relative To Drmentioning
confidence: 99%
“…As there is a reasonably large body of literature showing that hypoglycemia occurs more often among individuals treated with insulin than among those treated by pharmacotherapy or diet alone, one might reasonably expect to observe that individuals with insulin-treated diabetes are at higher risk for a motor vehicle crash when compared with individuals who control their diabetes by other means. Five of the 13 included studies provided separate crash risk data for drivers who were insulin-treated (Cox, 2003;Eadington & Frier, 1989;Laberge-Nadeau, 2000;Songer, 1988;Stevens, 1989) allowing us to estimate of the risk ratio associated with this subpopulation of drivers.…”
Section: Figure 1 Crash Risk In Drivers With Diabetes Relative To Drmentioning
confidence: 99%
“…In many (retrospective) studies, information is obtained through questionnaires, filled out by the drivers themselves (45)(46)(47)(48)(49)(50)(51)70,72,83,84). This can cause a recall bias on the one hand and a bias of subjectivity on the other hand.…”
Section: Questionnairesmentioning
confidence: 99%
“…Interestingly, the mileage-adjusted accident rate for the whole group was 5.4 per million miles driven (men 4.9, women 6.3), which was considerably lower than the accident rate for the general population of 10.0 accidents per million miles. Stevens et al (49) found, among 354 insulintreated diabetic drivers in Belfast, a similar accident rate of 7.9 per million miles, which was 7.8 in a control group. Since these rates were only calculated for the 24% of case and control subjects who reported accidents, true accident rates must have been lower (49).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Existing studies on diabetes and crash risks show contradictory results. In some studies, diabetes increased the risk of passenger vehicle crashes (8)(9)(10)(11); in others, there was either no effect (12) or even decreased risk (13,14). The study by Songer et al (15) estimates an additional number of crashes as a result of severe hypoglycemia if drivers using insulin were allowed to drive commercial motor vehicles (CMVs) in interstate commerce.…”
mentioning
confidence: 99%